2018
DOI: 10.1177/2050312118772475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of adverse events of renal impairment related to platinum-based compounds using the Japanese Adverse Drug Event Report database

Abstract: Objectives:Platinum compounds cause several adverse events, such as nephrotoxicity, gastrointestinal toxicity, myelosuppression, ototoxicity, and neurotoxicity. We evaluated the incidence of renal impairment as adverse events are related to the administration of platinum compounds using the Japanese Adverse Drug Event Report database.Methods:We analyzed adverse events associated with the use of platinum compounds reported from April 2004 to November 2016. The reporting odds ratio at 95% confidence interval was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…Hematologic and non-hematologic AE rates showed no significant difference in each regimen except patients in the ESHAP group had more renal impairment than the ICE group. This finding supported the database of the Japanese Adverse Drug Event Report that showed a higher risk of renal impairment of cisplatin compared with carboplatin and another platinum-based compound (reporting odds ratio 2.7, 95% CI 2.5–3.0) [ 18 ].…”
Section: Discussionsupporting
confidence: 84%
“…Hematologic and non-hematologic AE rates showed no significant difference in each regimen except patients in the ESHAP group had more renal impairment than the ICE group. This finding supported the database of the Japanese Adverse Drug Event Report that showed a higher risk of renal impairment of cisplatin compared with carboplatin and another platinum-based compound (reporting odds ratio 2.7, 95% CI 2.5–3.0) [ 18 ].…”
Section: Discussionsupporting
confidence: 84%
“…Recently, the Weibull distribution is used to detect the signals for adverse events by utilizing time-to-events date. [14][15][16][17] Thus, we evaluated the time-to-onset of ganciclovir-induced adverse events using Weibull distribution parameters. The results of both scale parameter α and shape parameter β of total adverse events in JADER suggested that ganciclovir-induced adverse reactions including cytopenia, leukopenia and liver damage develop early in most cases (the early failure type) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Disease names were defined using the Medical Dictionary for Regulatory Activities (MedDRA/J) version 24.0. According to a previous report [ 10 ], the following six preferred term was used for searching CDDP-associated acute kidney injury: “acute kidney injury,” “renal impairment,” “renal failure,” “renal disorder,” “renal function test abnormal,” and “renal tubular disorder.” Effect of 5-HT 3 RAs on CDDP-associated acute kidney injury was evaluated using the reporting odds ratio (ROR). To calculate the ROR, CDDP-associated acute kidney injury and all other reported adverse events associated with CDDP were defined as “cases” and “non-cases,” respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Disease names were defined using the Medical Dictionary for Regulatory Activities (MedDRA/J) version 24.0. According to a previous report [10], the following six preferred term was used for searching CDDP-associated acute kidney injury: "acute kidney injury, " "renal impairment, " "renal failure, " "renal disorder, " "renal function test abnormal, " and "renal tubular disorder. " Effect of Takemura et al Journal of Pharmaceutical Health Care and Sciences (2022) 8: 215-HT 3 RAs on CDDP-associated acute kidney injury was evaluated using the reporting odds ratio (ROR).…”
Section: Analyses On the Effect Of 5-ht 3 Ras On Cddp-associated Acut...mentioning
confidence: 99%